Effects of extremely low frequency electromagnetic fields on turkeys. (25th October 2017) - Laszlo, Anna M; Ladanyi, Marta; Boda, Krisztina; Csicsman, Jozsef; Bari, Ferenc; Serester, Andrea; Molnar, Zsolt; Sepp, Krisztian; Galfi, Marta; Radacs, Marianna
Abstract: Several studies have examined the potential biological effects of electromagnetic fields (EMF) on birds; however, little attention has been paid to the extremely low frequency (ELF; 0–300 Hz; 0–50 μT) radiation found in an urbanized environment. For monitoring the effects of ELF EMF, we used a turkey ( Meleagris gallopavo ) model, because the nucleated erythrocytes of turkeys contain β-adrenoceptors, and norepinephrine- (NE-) activated β-adrenoceptors have an important role in physiological and behavioral processes. Our aims were the following: 1) to investigate the intracellular mechanisms; 2) to compare the intracellular mechanisms in the treated and control groups over time, considering inter-individual differences and intra-subject correlations; 3) and to study the reversible nature of the response. The turkeys in the treatment group were treated in vivo with ELF EMF (50 Hz; 10 μT) for 3 wk after a 1-wk-long adaptation period. The animals were not exposed to ELF EMF during the regeneration period (5 wk following the exposure). The NE-activated β-adrenoceptor function was detected by measuring the amount of 3΄5΄-cyclic-adenosine-monophosphate (cAMP), and the biochemical enzyme parameters were defined. Repeated measurements of cAMP levels were analyzed using marginal models and a piecewise linear mixed model to compare treatment and control groups over time. According to our results, NE-activated β-adrenoceptor function was decreased in the treated birds in a time-dependent manner, while there were no differences between toxicological parameters in the serum, compared to the normal ranges. The decreased NE-dependent β-adrenoceptor function could be compensated by the homeostatic complex during the 5-wk regeneration period. Extended experimental periods and more sophisticated analysis methods may help prevent harmful environmental effects on birds; furthermore, these findings could affect public health and the economy.